“Partners rather than just providers…”: A qualitative study on health care professionals’ views on implementation of multidisciplinary group meetings in the North West London Integrated Care Pilot - Kassianos, Angelos P. (Int J Integr Care, 2015)
INTRODUCTION: Multidisciplinary group meetings are one of the key drivers of facilitating integrated care. Health care professionals attending such groups have a key role in the success of these discussions and hence, in the forming of multi-professional integrated care. The study aimed to explore the professionals’ experiences and views of participating and implementing the groups in integrated care context. METHODS: A qualitative study including 25 semi-structured interviews with professionals participating in the Northwest London Integrated Care Pilot analysed using thematic content analysis. RESULTS: Participants mentioned a number of benefits of participating in the meetings, including shared learning and shared decision-making between different services and specialties. Yet, they perceived barriers that diminish the efficiency of the groups, such as time constraints, group dynamics and technicalities. The participants felt that the quality of discussions and facilitation could be improved, as well as technical arrangements that would make them easier to participate. Most of the participants perceived the groups to be beneficial for providers mostly questioning the benefits for patient care. CONCLUSION: Findings provide an insight into how health professionals’ views of their participation to the multidisciplinary group meetings can be more effectively translated into more tangible benefits to the patients. To benefit patient care, the multidisciplinary groups need to be more patient-oriented rather than provider-oriented, while overcoming professional boundaries for participating.